KOMBINASI JENIS TANAMAN POLA DUSUNG PADA BERBAGAI KETINGGIAN TEMPAT DI NEGERI LUHU SERAM BARAT - Irwanto Irwanto; Jan W. Hatulesila; Moda Talaohu; Abdan Sukur Ely (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
This study aims to determine the structure and composition of plant species in Dusung land management in Luhu Village, discover the combination of plant species at various altitudes, and compare MPTS (Multi-Purpose Tree Species) plants and woods in the Dusung pattern. The sampling used the Stratified Sampling method, i.e., selecting locations based on altitude according to the research objectives and vegetation analysis carried out by the plot line method. For each altitude, 15 plots were made for each growth stage for vegetation sampling by recording the species, number, diameter at breast height (dbh) for the stage of poles and trees. The combination of the Dusung pattern plant species in Luhu Village is distinguishable at each altitude. Cloves are dominant at an altitude of >300-500 masl and >500 masl. The Sago tree stage is dominant at an altitude of 0-300 masl, while the dominant pole stage is Cocoa at 0-300 masl. The higher the site, the smaller the combination of plant species found in the Dusung Pattern in Luhu Village. The community prefers the combination of MPTS plants over wood species on Dusung in Luhu Village. The combination of plants in the Dusung Pattern research plot did not find short-lived plants (annual). It only found long-lived plants, i.e., trees (perennial) with a vegetation structure similar to a forest; therefore, it is more suitable to be called "Forest Garden".